Pola Adaptasi Gender dan Islam di Indonesia: Analisis Fenomenologi Etnik Madura - Nasiruddin, Muhammad; Zaki, Ade Rosi Siti (IAIN Syekh Nurjati Cirebon, 2023)
ABSTRACT: The adaptation patterns of gender and Islam in the Madurese community involve various cultural, religious, and historical factors that have shaped the social order and values within the community. These factors have influenced the efforts to adapt gender and Islam concepts to ensure women's equal rights and participation in economic independence, education, and other aspects. The paper aims to analyze these adaptation patterns within the context of the Madurese community, known for its rich and unique cultural characteristics, including gender roles and Islamic practices. The study reveals that Madurese society adapts gender roles and Islamic practices in accordance with their culture, as well as the social, cultural, and historical factors that influence these patterns. The research employs the phenomenological method to uncover various unique adaptation patterns, including the influence of patriarchal culture, customary values, and local religious traditions. These findings provide new insights into the dynamics of gender and Islam within the Madurese ethnic context and their relevance in an increasingly modern and global society.Keywords: The adaptation patterns, Gender, Islam, ethnicity, the Madurese community